2018
DOI: 10.31486/toj.17.0067
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Surgical Embolectomy for Massive Pulmonary Embolism Causing Intraoperative Cardiac Arrest

Abstract: Surgical embolectomy is a viable option for massive PE, and aerosolized epoprostenol can be used as adjuvant treatment for right ventricular strain secondary to acute pulmonary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…According to hemodynamic conditions, APE can be classified as (a) submassive, in presence of right ventricular dysfunction with a stable hemodynamic and (b) massive, when severe right ventricular dysfunction leads to an unstable hemodynamic up to severe cardiogenic shock 5 4,5 . Treatment options include systemic anticoagulation, thrombolysis, and surgical embolectomy 3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to hemodynamic conditions, APE can be classified as (a) submassive, in presence of right ventricular dysfunction with a stable hemodynamic and (b) massive, when severe right ventricular dysfunction leads to an unstable hemodynamic up to severe cardiogenic shock 5 4,5 . Treatment options include systemic anticoagulation, thrombolysis, and surgical embolectomy 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options include systemic anticoagulation, thrombolysis, and surgical embolectomy 3 . Despite recent surgery being a contraindication for thrombolysis because of the high risk of bleeding, APE can be a life‐threatening condition and, therefore, in some selected cases, thrombolysis can also be indicated in APE after recent surgery, especially in the thoracic field, with satisfactory results 1,5‐7 . Sakuragi et al 7 reported one case of bleeding out of six patients treated with systemic anticoagulation and/or thrombolysis for pulmonary embolism following pulmonary resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation